2010
DOI: 10.1098/rsta.2010.0047
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and geomorphological hazards in the eastern European Alps

Abstract: Climate and environmental changes associated with anthropogenic global warming are being increasingly identified in the European Alps, as seen by changes in long-term highalpine temperature, precipitation, glacier cover and permafrost. In turn, these changes impact on land-surface stability, and lead to increased frequency and magnitude of natural mountain hazards, including rock falls, debris flows, landslides, avalanches and floods. These hazards also impact on infrastructure, and socio-economic and cultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
127
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(131 citation statements)
references
References 64 publications
1
127
0
3
Order By: Relevance
“…In the European Alps, population and infrastructure growth provides the impetus for better understanding of the pattern of landsliding, triggers, and efforts required to reduce landslide risk. The climate of the region is changing, and this has been implicated in increased landslide risk (Borgatti and Soldati 2010;Crozier 2010;Keiler et al 2010). While understanding the spatial distribution of past landslides can help to facilitate better understanding of regional landslide impacts and triggers, such an analysis can only be obtained through the use of regional-scale landslide inventories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the European Alps, population and infrastructure growth provides the impetus for better understanding of the pattern of landsliding, triggers, and efforts required to reduce landslide risk. The climate of the region is changing, and this has been implicated in increased landslide risk (Borgatti and Soldati 2010;Crozier 2010;Keiler et al 2010). While understanding the spatial distribution of past landslides can help to facilitate better understanding of regional landslide impacts and triggers, such an analysis can only be obtained through the use of regional-scale landslide inventories.…”
Section: Introductionmentioning
confidence: 99%
“…Landslides are a serious geomorphological hazard in many of the world's mountain regions (Keiler et al 2010;Malet et al 2010). In the European Alps, population and infrastructure growth provides the impetus for better understanding of the pattern of landsliding, triggers, and efforts required to reduce landslide risk.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, the arising discussion related to possible impacts of climate change on the magnitude and frequency of mountain hazards (Keiler et al 2010) resulted in a rising scientific debate on the spatiotemporal evolution of elements at risk exposed (e.g., Hufschmid et al 2005;Fuchs and Bründl 2005;Keiler et al 2006). As a consequence it may be postulated that risk awareness of the general public and administrative bodies responsible for hazard protection has risen (Commission of the European Communities 2007).…”
Section: Resultsmentioning
confidence: 99%
“…There is a strong scientific evidence of an increase in mean precipitation, and magnitude and frequency of extreme precipitation events, which implies that extreme flood events might become more frequent (Christensen and Christensen 2003;Kundzewicz et al 2005;Solomon et al 2007;Keiler et al 2010). In parallel, exposure to floods might increase across Europe as well as flood vulnerability due to population and wealth moving into flood-prone areas.…”
Section: Introductionmentioning
confidence: 99%
“…Short duration of unusually warm events (e.g. the 2003 heatwave) seemed to be particularly important for slope failures (see also Keiler et al 2010;Ravanel & Deline 2011). Similarly Delaloye et al (2008) and Roer et al (2008) observed an acceleration of several rock glaciers in the Valais Alps since the 1990s, probably linked to permafrost warming.…”
Section: Introduction: Sediment Transfers and Mountain Complex Systemsmentioning
confidence: 95%